False positive results for antibody to HIV in two men with systemic lupus erythematosus. Issue 9 (September 1992) - Esteva, M H; Blasini, A M; Ogly, D; Rodríguez, M A
Abstract : False positive results were obtained for HIV tests in two men with active systemic lupus erythematosus (SLE) who were suspected of being infected with HIV because of fever, weight loss, lymphadenopathy, and inflammatory myopathy. Enzyme linked immunosorbent assays (ELISAs) for HIV were twice positive when tested three times over a period of six months. Western blot analysis showed reactivity against the gp41 band in patient 1. False positive results for HIV tests can occur in patients with SLE, potentially leading to an erroneous diagnosis of HIV infection.